An Analysis of The Old Man and the Sea in Christian, Universal and Buddhist Perspectives - Amporn Sa-ngiamwibool (Universitas Sanata Dharma, 2016)
Religion and literature share universal senses that touch human mind. The Old Man and the Sea by Ernest Hemingway, a Pulitzer-award and-Nobel-prize winner, which is full of Christianity symbols and allusions, is selected to verify this universality, with three specific purposes which aimed to analyze and draw out: 1) Christian symbols and allusions, 2) universal senses of life, and 3) Buddhist essence in the novella. The analysis revealed these findings. All symbols and allusions relate to Christ. The attempt to fight against inevitable destiny that is a universal and natural order of life touches the mind. The novella implicated two cores of Buddhist essence: the four noble truths and the eightfold path. It could be concluded that the line between literature and religion share universality which lies in human mind, regardless of religious beliefs.